Regulatory Role of N6-methyladenosine (m6A) Modification in Osteosarcoma - Zhang, Yujie; Wang, Yanyan; Ying, Liwei; Tao, Sifeng; Shi, Mingmin; Lin, Peng; Wang, Yangxin; Han, Bin (Frontiers in Oncology, 2021)
Osteosarcoma is the most common primary bone malignancy, typically occurring in childhood or adolescence. Unfortunately, the clinical outcomes of patients with osteosarcoma are usually poor because of the aggressive nature of this disease and few treatment advances in the past four decades. N6-methyladenosine (m6A) is one of the most extensive forms of RNA modification in eukaryotes found both in coding and non-coding RNAs. Accumulating evidence suggests that m6A-related factors are dysregulated in multiple osteosarcoma processes. In this review, we highlight m6A modification implicated in osteosarcoma, describing its pathophysiological role and molecular mechanism, as well as future research trends and potential clinical application in osteosarcoma.